PENGARUH CITRA MEREK, CITRA PERUSAHAAN DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE MEREK SAMSUNG (Studi Pada Mahasiswa Fakultas Ekonomi Universitas Islam Malang) - Suparman Suparman; Rois Arifin (E-JRM : Elektronik Jurnal Riset Manajemen, 2017)
ABSTRACTTarget of this research is to know influence brand image, company image and product quality by simultan to decision purchasing smartphone Samsung and influence brand image, company image and product quality by parsial to decision purchasing smartphone Samsung. This research type is research explanatory. This research done at University of Islamic Malang. Population in this research is all students Faculty Economics University of Islamic Malang year 2013-2016 amounting to 2435 student while research sampel amount 96 student with sampling technique purposive sampling method. Result of research indicate that brand image, company image and product quality have an effect by simultan to decision purchasing of Samsung smartphone. Brand Image, company image and product quality by parsial have an effect to decision purchasing of Samsung smartphone.Keywords : Brand Image, Company Image, Product Quality, Decision Purchasing